PENGARUH EKSTRAK ETANOL BUNGA, DAUN, DAN AKAR KEMBANG SEPATU (Hibiscus rosa sinensis) TERHADAP BERAT, VOLUME, DAN DIAMETER TUBULUS SEMINIFERUS MENCIT (Mus musculus) - Rojib Rojib; Sukarjati Sukarjati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
Hibiscus (Hibiscus rosa sinensis) many are grown as ornamental plants, shrubs, and grown in the tropics andsubtropics. Hibiscus is also one kind of plant that is potentially as antifertility. Types of bioactif compoundscontained in plants, the main compounds that are derived from the steroids, alkaloids, isoflavanoid,tripernoid, and activity as xanthon antifertilities. This encourages the researcher to know the influence ofethanol ekstract flowers, leaves, and roots of hibiscus (Hibiscus rosa sinensis) against the weight, volumeand diameter ofseminiferoustubules mice (Mus musculus). The sample of this research is the mice by asmuch as 27 tail with a weight of 20-30 grams, aged 2.5 months. Murine in to 3 groups, each group is divided3 treatment. As for the treatments given are extracts of flowers, leaves, and roots of hibiscus with dosecontrol, 150, and 300 mg/kg. Granting of extracts for 35 days. On day 37 mice are in surgery for testicularweight to observations taken, the volume of the testes. The testes then made preparations and measureddiameter of seminiferoustubules. This research is experimental research using Random Design Group. Thedata obtained were analyzed with variant analysis (ANOVA) in one direction and continued with test LSD(Least Significant Different). The results of the research there shows the influence of the ethanol extracts offlowers, leaves, and roots of hibiscus against testicular volume, weight, and diameter of seminferoustubules (P < 0.05). The best treatment that can decrease the weight, volume and diameterofseminiferoustubules is on the flower with a dose of 300 mg/kg. The results of this research it can beconcluded that extracts of flowers, leaves, and roots can lose weight, testicular volume and diameter ofseminiferoustubules. In future it is hoped the research could be developed as material antifertilitas in men. Keywords:Extract of flower, Laves, roots of (Hibiscus rosa sinensis), testicles, diameter of seminiferous tubules, mice (Mus musculus).